Cognitive Conflict of Relational Learners in Connecting Proportion Concepts on Three Term Ratio Problems - Ratnah Lestary; Subanji; Iqbal Ramadani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The study's purpose is to describe the cognitive conflicts experienced by students with relational understanding when solving the problem of three-term ratios. The current research is a case study with a qualitative approach using a purposeful sampling technique. The three research objects are representations of the condition that (1) the student was sure of his solution (cognitive conflict was solved) and the solution is correct, (2) the student was confident with his solution (cognitive conflict was solved) but the solution is not correct, and he is not confident with the solution (cognitive conflict was not solved), and the solution was not correct. The results of this study describe students with relational understanding experience cognitive conflicts, that is, being aware of the conflict between the initial concepts they have and the results obtained. Students feel doubtful and worried, as indicated by the awareness that the initial scheme applied to one proportion problem cannot be applied to other comparison questions. Students' cognitive conflicts with relational understanding do not always lead them to get the correct solution to the three-term ratio problems. The reason is that the student believes comparison is wrong (misconception).